MENINGKATKAN KEMAMPUAN PENGUASAAN KONSEP DAN METODE PEMBELAJARAN MATEMATIKA DENGAN PAIKEM BERBASIS ICT BAGI GURU MADRASAH IBTIDAIYAH (MI) - Romadiastri, Yulia (At-Taqaddum, 2016)
To improve the quality of mathematics learning, Madrasah Ibtidaiyah in district  Ngaliyan  has conducted  various types of activities, one of the efforts was to form a working group on teachers (KKG). As a result,  madrasah  teacher  empowerment  especially in  mathematics  learning both in concept  and mastery learning methodologies are not as expected.  KKG as formal institution that hosts MI teachers need to be empowered with the support of various parties. Problems occurred  was a classroom teacher MI less mastered the concept of  integrative  mathematics so there was some misconception of the material  and they also has limited knowledge of the variation of  mathematics  learning method in a fun, meaningful and engaging the liveliness of the learners according scientific approach. The phases program public service performed are: (1) brainstorming and (2) training. The result of these  outreach programs include: training  PAIKEM Learning and Contextual  ICT Media for the teachers who are members of KKG MI  Subdistrict  Ngaliyan goeswell. Participants who attend the training look very  enthusiastic  because  theyrarely  get  similar  training.From the results of training obtained by awide range of new knowledge  about learning math in an active and funway.  Producing a contextual ICT media for learning mathematics. Brainstorming is done against the commitee of KKG MI Ngaliyan and greeted with enthusiasm, especially with the offer of assistance and cooperation with the Department of Mathematics Education of the Faculty of Science and Technology UIN Walisongo Semarang.